Red Clover HDT, a BAHD Hydroxycinnamoyl-Coenzyme A:L-3,4-Dihydroxyphenylalanine (L-DOPA) Hydroxycinnamoyl Transferase That Synthesizes Clovamide and Other N-Hydroxycinnamoyl-Aromatic Amino Acid Amides - Sullivan, Michael L.; Knollenberg, Benjamin J. (Frontiers in Plant Science, 2021)
Red clover leaves accumulate high levels (up to 1 to 2% of dry matter) of two caffeic acid derivatives: phaselic acid (2-O-caffeoyl-L-malate) and clovamide (N-caffeoyl-L-3,4-dihydroxyphenylalanine [L-DOPA]). These likely play roles in protecting the plant from biotic and abiotic stresses, but can also help preserve protein during harvest and storage of the forage via oxidation by an endogenous polyphenol oxidase. We previously identified and characterized HMT, a hydroxycinnamoyl-coenzyme A (CoA):malate hydroxycinnamoyl transferase from red clover. Here, we identified a hydroxycinnamoyl-CoA:L-DOPA hydroxycinnamoyl transferase (HDT) activity in unexpanded red clover leaves. Silencing of the previously cloned HMT gene reduced both HMT and HDT activities in red clover, even though the HMT enzyme lacks HDT activity. A combination of PCR with degenerate primers based on BAHD hydroxycinnamoyl-CoA transferase sequences and 5' and 3' rapid amplification of cDNA ends was used to clone two nearly identical cDNAs from red clover. When expressed in Escherichia coli, the encoded proteins were capable of transferring hydroxycinnamic acids (p-coumaric, caffeic, or ferulic) from the corresponding CoA thiolesters to the aromatic amino acids L-Phe, L-Tyr, L-DOPA, or L-Trp. Kinetic parameters for these substrates were determined. Stable expression of HDT in transgenic alfalfa resulted in foliar accumulation of p-coumaroyl- and feruloyl-L-Tyr that are not normally present in alfalfa, but not derivatives containing caffeoyl or L-DOPA moieties. Transient expression of HDT in Nicotiana benthamiana resulted in the production of caffeoyl-L-Tyr, but not clovamide. Coexpression of HDT with a tyrosine hydroxylase resulted in clovamide accumulation, indicating the host species’ pool of available amino acid (and hydroxycinnamoyl-CoA) substrates likely plays a major role in determining HDT product accumulation in planta. Finally, that HDT and HMT proteins share a high degree of identity (72%), but differ substantially in substrate specificity, is promising for further investigation of structure-function relationships of this class of enzymes, which could allow the rational design of BAHD enzymes with specific and desirable activities.